2019
DOI: 10.1136/jclinpath-2019-206310
|View full text |Cite
|
Sign up to set email alerts
|

How many serial sections are needed to detect apoptosis in endoscopic biopsies with gastrointestinal graft versus host disease?

Abstract: AimsThe hallmark histological feature of acute gastrointestinal graft versus host disease (GI GVHD) is epithelial apoptosis. This is the first formal evaluation of how many serial sections are required to consistently detect apoptotic bodies in endoscopic biopsies from various GI locations in patients with clinically validated GI GVHD.Methods, results and conclusionsAssessment of 1008 serial sections showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…We found that higher maximum histological grades under any system correlated strongest with steroid therapy. However, we could not establish a histological cut-off to differentiate clinically insignificant aGvHD from significant counterparts by quantifying apoptotic bodies [ 14 , 21 ], even though the apoptotic body counts correlated with the application of steroid therapy. An increase in apoptotic bodies was observed in patients without clinically apparent intestinal aGvHD who had macroscopically bland mucosa; this is consistent with our previously published data [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that higher maximum histological grades under any system correlated strongest with steroid therapy. However, we could not establish a histological cut-off to differentiate clinically insignificant aGvHD from significant counterparts by quantifying apoptotic bodies [ 14 , 21 ], even though the apoptotic body counts correlated with the application of steroid therapy. An increase in apoptotic bodies was observed in patients without clinically apparent intestinal aGvHD who had macroscopically bland mucosa; this is consistent with our previously published data [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, there are competing diagnostic and grading systems for colon aGvHD, with the Lerner [ 11 ], Sale [ 12 ], and Melson [ 13 ] methods being the most popular; to date, these have not been compared with respect to their diagnostic accuracy and prognostic impact. Second, previous analyses are generally based on a single biopsy per patient only [ 6 , 7 , 14 ]; this disregards the variations in aGvHD manifestations throughout the colon, which are profound [ 8 10 , 15 ]. Thus, evaluating multiple biopsy sites per patient using the most appropriate diagnostic system would greatly enhance the histological assessment of aGvHD, thereby guiding both patient management as well as further scientific exploration.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of granulomas was also assessed in all GI biopsies from two retrospective cohorts of haematopoietic transplant patients: (i) patients with clinically and histologically validated GI GVHD from another study 7 ; and (ii) all patients who had received UCB at the BMTU over a 7-year period.…”
Section: Methodsmentioning
confidence: 99%
“…In the current research, we have already seen the potential of MSC-ApoVs in disease regulation, tissue regeneration, and drug delivery. There are other roles for ApoVs, such as disease diagnosis [82][83][84] and vaccine development. [51] More functions and applications for MSC-ApoVs are yet to be discovered by researchers.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%